ANALISIS PERTUMBUHAN DAN KETIMPANGAN ANTAR KABUPATEN/KOTA DI PROVINSI KALIMANTAN TIMUR TAHUN 2001-2009 - Devi Yanti Rahayu S; Mulyo Hendarto (Universitas Diponegoro, 2012)
ABSTRACT Any economic development expects the creation of high economic growth and equity. East Kalimantan province from the year of 2001-2009 shows the economic growth is volatile and tends to decline on average by 2,77 percent while economic growth in the district / city looks lame, some are experiencing positive growth and even negative, while the differences of GDP per capita are quite striking between regions. This shows the disparity between urban districts in the province of East Kalimantan. This study aims to analyze the income’s disparity that occurred between the district / city in East Kalimantan Province in the year of 2001-2009. The data used for this study is secondary data. Meanwhile, The analytical method used was Typology Klassen, and Williamson index. Based on the Analysis of Klassen Typology shows the majority of as nine district / city include the fast growing area. These results indicate that during the year between 2001-2009 had occured disparity and fluctuated annually and tend to decline, but still relatively high in East Kalimantan province with an average of 0,828. The highest disparity occurred in 2001 at 0,916 and the lowest disparity occurred in the year of 2009 at 0,731.